PROBLEM BASED LEARNING TO IMPROVE STUDENTS WRITING ABILITY - Jenny Ika Misela; Mahendra Puji Permana Aji (Pedagogic Research-Applied Literacy Journal, 2025)
This study is aimed at implementing PBL to improve the students’ writing ability. It was conducted by using classroom action research which has two cycles. Each cycle has 4 steps including planning, acting, observing, and reflecting. The instrument used in this research was qualitative and quantitative instrument. Qualitative instruments that she used is observation check list and field notes. The quantitative data was gotten from the students’ score of posttests from cycle 1 and cycle 2. The questionnaire was used in this research as a preliminary study. The subject of the research was the students of tenth grade SMA Wahidiyah Kediri which consist of 29 students. Based on writing test scores, in the pre-liminary study, there were only 4 % of the students who passed the minimum standard score. After that, the score of the students who passed the test in cycle 1 was 13% and 78% of the students passed the test in cycle 2.  Based on the observation sheet and field notes, it was found that the learning process of writing runs well. The students could follow the step of PBL orderly begin from (1) clarifying and agreeing on terms and concepts that are unclear¸ (2) formulating the problem, (3) analyzing the problem, (4) formulating hypothesis, (5) collecting data, (6) evaluating the hypothesis, (7) formulating the recommendation of problem solving. The result of the research shows that PBL method can improve the students writing ability and it is supported by using pictures and outline.